Polish patients’ opinion on the preparation of midwives to provide advice on the symptoms of pregnancy (part I) - Iwanowicz-Palus, Grażyna; Golonka, Ewa; Bień, Agnieszka; Stadnicka, Grażyna (Nursing Problems / Problemy Pielęgniarstwa, 2012)
Introduction. During pregnancy, regardless of its course (physiological or not), there may appear certain ailments such as: nausea and vomiting, heartburn, constipation, frequent urination, vaginal discharge, swelling, syncope, varicose veins, bleeding, fatigue, irritability and symptoms shortness of breath. A midwife should be able to educate the pregnant woman about common problems that occur during pregnancy and ways in which they should be prevented and what to do if they occurs. Aim of the study. Attempt to explore the Polish public opinion on the level of preparation of midwives to advise on the most common symptoms accompanying pregnancy. Materials and methods. The study was conducted since February to May 2011, among 505 respondents (293 women and 212 men) living in the eastern region of the country. The study was conducted using diagnostic survey, using questionnaire techniques. The research tool was a questionnaire survey developed basing on a five point Likert scale. Results and conclusions. Respondents believe that midwives have the knowledge to deal with situations of the most common complaints of pregnancy and are prepared to provide guidance in case of nausea and vomiting (90.27%), constipation (79.01%), frequent urination (78.41 %), vaginal discharge (75.44%), edema (73.86%), fatigue, irritability and symptoms of dyspnea (72.67%), bleeding (70.5%) and varices (68.52%). Lack of knowledge on the level of prepararation of midwives to provide advice on the symptoms that occur during pregnancy characterizes mainly (p 0.05).